TERMS USED IN THE PROCESS OF LEARNING VOLLEYBALL AND THEIR EXPLANATION - Abdumumin Tursunov (Modern American Journals, 2025)
This article will provide information about the most important concepts and terms encountered in the process of theoretical and practical study of volleyball. The need for this is due to the training of practicing volleyball players, as well as the content of interpreted concepts and terms in the existing methodological literature.
Keywords: Tactical actions, game tactics, physical qualities, sports competitions, competitive activities.